Pengaruh Foreign Direct Investment, Indeks Kemahalan Kontruksi Dan Tingkat Pengangguran Terbuka Terhadap Tingkat Kemiskinan Di Indonesia Tahun 2015-2024 Dalam Perspektif Ekonomi Islam - Liana Nurul Fatmah; Madnasir; Nur Wahyu Ningsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study analyze the influence of Foreign Direct Investment (FDI), the Construction Cost Index (CCI), and the Open Unemployment Rate (TPT) on the Poverty Rate in Indonesia for the 2015-2024 period from an Islamic economic perspective. The method used is an associative quantitative approach with secondary data from BPS and BKPM, the analysis was conducted with panel data regression using the Fixed Effect Model (FEM). The results show that foreign direct investment has a negative and insignificant effect on the poverty rate, the construction cost index has a positive and significant effect on the poverty rate, and the open unemployment rate has a positive and significant effect on the poverty rate. Simultaneously, all three have a significant effect on the poverty rate. In Islamic economics, the stability of foreign direct investment, the construction cost index, and the open unemployment rate is important for justice (al-adl) and welfare (maslahah) in the management of economic resources. The government is expected to be able to direct investment policies, control the cost of living, and create productive jobs in order to reduce poverty and improve welfare.